The pericarp and its surface wax layer in maize kernels as resistance factors to fumonisin accumulation by Fusarium verticillioides - Sampietro, Diego Alejandro (2009)
Fusarium verticillioides causes maize ear rot and contaminates kernels with fumonisin mycotoxins in Argentina. The aim of this work was to elucidate if the kernel pericarp and its surface wax layer are resistance factors to fumonisin accumulation in maize genotypes from Argentina. Fourteen maize genotypes were inoculated with F. verticillioides in laboratory assays. Intact kernels of genotypes resistant to fumonisin accumulation in the field had the lowest mycotoxin concentration in the current assays suggesting that kernel factors are involved. Intact kernels of landraces, breeding populations and L4637 inbreed were less susceptible than wounded ones, suggesting that intact kernel pericarp restricted fumonisin accumulation. Removing wax from the pericarp significantly increased fumonisin concentration and a higher wax content on kernels was associated to lower fumonisin accumulation. Our results suggest that the pericarp and its wax content are resistance factors to fumonisin accumulation in most genotypes assayed. Nevertheless, other kernel factors could not be excluded.